Accounting Development in the System of Transition to the New Standards of Financial Security of a Commercial Bank - A. V. Lukyanov (Учёт. Анализ. Аудит)
The article describes the features of the evolution theory in the system of statistical accounting of commercial bank’s financial security. Based on the analysis of the globalization processes the necessity was justified to plan at any level of financial control system macroeconomic factors of (or threats to) security of the financial state of the object. In the work there were used the methods of graphical data modeling of economic processes and their algorithms. This made it possible to integrate in the study not only literary analysis and the regulatory framework analysis, but also to expand the scope of the study to statistically significant indicators on the basis of the analysis of the fundamental accounting methodology and perspective accounting methodology in the system of transition to the new commercial bank financial security standards. The article examines the existing approaches to understanding the essence of financial security and shows their weaknesses. The article offers to use static and active approaches to the interpretation of the concept of financial security and shows the duality of standards of its evaluation which are operating in the state. This provided us with an opportunity to identify the scientific gap in the accounting system for banks with basic (or internal) license and show the prospects of its neutralizing by accounting methods. The author has proved the need to implement forecasting tools in the current system of accounting of the financial security of the Bank. The author developed a matrix of compliance to the regulations and scientifically-practical methods for controlling commercial bank financial security as part of adapting to the international practice. So, there was the comparative analysis of the core performance indicators characterizing the financial security mainly associated with the functioning of the financial sector of the national economy and it also showed the gaps existing in the Russian Federation system as the basis for further development of the simplified system of statistical accounting of financial security for the banks in the Russian Federation.